Relevansi al-qur’an surah luqman ayat 12-13 dan 16-19 dengan keterampilan konselor pada konseling anak - Kirana, Desi Candra (Maliki Interdisciplinary Journal, 2023)
Counseling children is a process of providing assistance by counselors with children that aims to help children understand what has happened to them, so that a child can complete his developmental tasks properly and optimally, besides that so that children are able to develop their potential. The purpose of writing this article is to find out the urgency of good intervention by counselors in counseling children according to the instructions in the Al-Qur’an surah Luqman from the story of the wisdom of Luqman Al-Hakim’s example. So that counselors can realize that their competence to limit empowerment, knowledge, change and improvement is important. In addition, so that readers can better understand and be able to practice the teachings in the Qur’an. There is relevance between the concept of child counseling in the Qur’an in the story of Luqman Al-Hakim and the competence of counselors in providing counseling. As in the aspects of empowerment, understanding, change and improvement. Counselors are also expected to be able to build positive relationships with clients through good communication, provide interventions with gentleness that is weak and do not use violence, provide good advice, provide understanding regarding the consequences of the behavior carried out, and provide direction on things that have a positive impact on the client.